The Influence of Lifestyle and Hedonism on Impulse Buying with Self-Control as a Moderation Variable - Mita, Mita; Hesi Eka Puteri (SKeTsa Bisnis (e-jurnal), 2025)
Introduction; The problem studied in this research is the effect of lifestyle and hedonism attitudes on impulse buying, with self-control as a moderating variable. The purpose of this study is to determine and analyze these effects among Generation Z Muslims in Bukittinggi City. Method; This research is field research with a quantitative approach. Data were collected through direct observation by distributing questionnaires. The sample consisted of Generation Z in Bukittinggi City. Data processing was done using SPSS 26. Analytical tools included instrument tests (reliability and validity), classical assumption tests (normality, autocorrelation, multicollinearity, heteroscedasticity), and hypothesis testing using t-test, F-test, and moderated regression analysis (MRA). Result; The results showed that the lifestyle variable significantly affects impulse buying (significance value 0.104 < 0.05). Hedonism attitude also significantly affects impulse buying (significance value 0.000 < 0.05). Moderation analysis revealed that self-control significantly moderates the relationship between lifestyle and impulse buying (coefficient = -0.064, significance = 0.00 < 0.05), indicating that stronger self-control weakens the effect of lifestyle on impulse buying. However, self-control does not moderate the relationship between hedonism attitude and impulse buying (coefficient = -0.024, significance = 0.131 > 0.05). Conclusion; Self-control plays a moderating role in the influence of lifestyle on impulse buying among Generation Z Muslim fashion consumers in Bukittinggi City, weakening this effect. However, self-control does not moderate the influence of hedonism attitudes on impulse buying.